2002
DOI: 10.1103/physrevlett.88.133003
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Gradient Focusing and Deceleration of a Molecular Beam

Abstract: Neutral dipolar molecules can be decelerated and trapped using time-varying inhomogeneous electric fields. This has been demonstrated only for molecules in low-field seeking states, but can, in principle, be performed on molecules in high-field seeking states as well. Transverse stability is then much more difficult to obtain, however, since molecules in high-field seeking states always experience a force towards the electrodes. Here we demonstrate that an array of dipole lenses in alternate gradient configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 28 publications
1
118
1
3
Order By: Relevance
“…In addition, with this linear geometry, it is possible to load hfs molecules directly into the trap. The linear trap could be equally well combined with an alternate gradient (AG) decelerator 9,14 for molecules in hfs states. This would widen the scope of the species amenable to deceleration and efficient trapping to large molecules, which possess only hfs states.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with this linear geometry, it is possible to load hfs molecules directly into the trap. The linear trap could be equally well combined with an alternate gradient (AG) decelerator 9,14 for molecules in hfs states. This would widen the scope of the species amenable to deceleration and efficient trapping to large molecules, which possess only hfs states.…”
Section: Introductionmentioning
confidence: 99%
“…Other electrode geometries can be used to select neutral molecules or clusters, e.g., the electric quadrupole filter or the alternating gradient decelerator 22,[38][39][40] . These devices, however, are significantly larger (>1 m) and much more complex to manufacture and install.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that this technique can be successfully applied to this "unfavourable" molecule [6], which has a comparatively small ratio of Stark shift to initial kinetic energy and therefore requires a large number of deceleration stages. The application of Stark deceleration on similar molecules was also demonstrated before with YbF [7], with a different type of Stark decelerator [8].…”
Section: Introductionmentioning
confidence: 97%
“…To deplete the total kinetic energy of the molecule several deceleration stages (each removing ∆E) are required, for which the switching is repeated. With a modified geometry of electrodes and switching sequence, molecules in high field seeking states can also be decelerated [7,8].…”
Section: Principlementioning
confidence: 99%